2022
DOI: 10.21203/rs.3.rs-1856661/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Possible high-Tc superconductivity exceeding 100 K in Ir-substituted perovskite-type manganese oxides

Abstract: The search for new high-Tc superconductors has commonly focused on layered perovskite compounds with isoelectronic or isostructural properties similar to those of cuprates.1, 2 For example, in 2019, a family of 3d nickel-based superconductors (Nd, Sr)NiO2 was discovered by Hwang et al.3More recently, Ca2RuO4, a 4d transition metal oxide, received attention as a superconductor with Tc = 64 K in coexistence with ferromagnetism in nanofilm single crystals.4 Even the 5d transition metal oxide Sr2IrO4 was thoroughl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…We found that the dopant and its nearest Ta are separated by 2.46 Å, whereas the nearest Li has the relatively short Li-Li bond lengths of 2.03 Å. The latter seems to be crucial for the n-doped perovskite oxides in the context of their recently discovered high-temperature superconductivity exceeding 100 K [25].…”
Section: Electron Density Induced By the LI Dopantmentioning
confidence: 76%
“…We found that the dopant and its nearest Ta are separated by 2.46 Å, whereas the nearest Li has the relatively short Li-Li bond lengths of 2.03 Å. The latter seems to be crucial for the n-doped perovskite oxides in the context of their recently discovered high-temperature superconductivity exceeding 100 K [25].…”
Section: Electron Density Induced By the LI Dopantmentioning
confidence: 76%
“…The perovskite CaTiO 3 was discovered in 1839 by Gustav Rose, fortuitously starting a debate lasting over a hundred years about the general crystal structure of perovskites. , Since then, perovskites have been a topic of intense research for a multitude of features, from high-temperature superconductivity, giant magnetoresistance, and oxide fuel cells to efficient solar cells. , Especially, they have been shown to host exceptionally high quantum efficiency in terms of their optoelectronic performance. This combined with the presence of spin–orbit interaction, particuarly strong in lead halide based perovskites, and a resulting broken spin degeneracy makes them highly appealing for spin-optoelectronic devices. However, an indisputable challenge to their application is the (photo)degradation of perovskites resulting in a notably short device lifetime . In recent years, layered two-dimensional (2D) perovskites have emerged as a viable alternative, as several groups have reported an increase in lifetime of 2D perovskite devices. Being two-dimensional by design, it is relatively straightforward to exploit quantum confinement effects to tune their band gap by adjustment of the layer number, making them perfectly suited for multijunction devices .…”
mentioning
confidence: 99%